Comparing topsoil charcoal, ash, and stone cover effects on the postfire hydrologic and erosive response under laboratory conditions. (2nd February 2018) - Prats, Sergio Alegre; Abrantes, João Rafael Cardoso de Brito; Coelho, Celeste de Oliveira Alves; Keizer, Jan Jacob; de Lima, João Luis Mendes Pedroso
Abstract: Wildfires typically transform vegetation and litter into a heterogeneous layer of ash and charred material covering the soil surface that can substantially modify the postfire hydrological and erosive response. To further elucidate the influence of postfire covering layers on sheet and concentrated flow erosion, we carried out laboratory rainfall and inflow simulations on 5 distinct soil surface conditions: bare soil, with a protective cover of char, ash, stones, and a combination thereof simulating field conditions. Each of 3 replicate simulations per treatment involved 4 runs, the first 2 simulating just rain (at 56 mm hr −1 ) under dry and wet soil conditions and the next 2 simulating rain together with inflow at high and extreme rates (0.76 and 1.4 L min −1 ). Overall runoff over the 4 runs together was lower for all 4 types of protective cover than for bare soil, but ash and char were clearly less effective than stones and, in particular, field conditions with runoff reductions of 25%, 23%, 40%, and 70%, respectively. Stones and field conditions were similarly effective in reducing overall erosion rates (with 47% and 77%, respectively), whereas ash and char even slightly increased overall erosion rates compared to bare soil. Ash and char were effective in reduction erosion but only during the first 2 runs under simulated rainfall. The greater effectiveness of the field conditions suggested synergistic effects between its 3 components, probably due to the stones enhancing infiltration and increasing flow resistance, thereby hampering detachment of ash and char and/or enhancing their deposition.